The Future for Transcatheter Aortic Valve Implantation. Issue 28 (29th October 2015) - Vinall, Phil
Transcatheter aortic valve replacement is surpassing surgical aortic valve replacement as the procedure of choice for aortic valve repair due to improvements in prosthesis and delivery system technology, operator experience, better patient selection, and reduced complication rates, including stroke, bleeding, paravalvular aortic regurgitation, the need for a permanent pacemaker, and all-cause mortality.